DAMPAK PROGRAM REVITALISASI PASAR TERHADAP PENDAPATAN PEDAGANG - Ni Putu Mia Saraswati; Ida Ayu Nyoman Saskara; Sudarsana Arka (Buletin Studi Ekonomi, 2025)
The trade center is one indicator of community economic activity. Currently, there are two types of goods markets that are developing, namely traditional markets and modern markets. The emergence of modern shopping centers such as minimarkets, supermarkets, and hypermarkets is disrupting the existence of traditional markets. The similarity of functions between modern shopping centers and traditional markets has given rise to competition between the two. The purpose of this study was to determine the impact of the market revitalization program on increasing the income of traders at the Petang Market, Badung Regency. The number of samples taken were 61 traders. Data was collected based on the results of observations, in-depth interviews and structured interviews. This study uses the Wilcoxon test to examine the impact of the revitalization program on the income of traders at the Petang Market, Badung Regency. Based on data processing regarding the impact of traditional market revitalization on traders' income, the Asymp.Sig value is obtained. (2-Tailed) is 0.008 and for the one-tailed test value the number is divided in half so that it becomes 0.004 then H1 is accepted. This means that there is an increase in the income of traders after the implementation of the revitalization program at the Petang Market, Badung Regency.     Pusat perdagangan merupakan salah satu indikator kegiatan ekonomi di masyarakat. Saat ini terdapat dua jenis pasar barang yang telah berkembang yaitu pasar tradisional dan pasar modern. Eksistensi pusat perbelanjaan modern seperti minimarket, supermarket hingga hipermarket mengusik keberadaan pasar tradisional. Kesamaan fungsi yang dimiliki oleh pusat perbelanjaan modern dan pasar tradisional menimbulkan persaingan antara keduanya. Tujuan dilakukannya penelitian ini adalah untuk mengetahui dampak program revitalisasi pasar terhadap peningkatan pendapatan pedagang di Pasar Petang Kabupaten Badung. Jumlah sampel yang diambil yaitu 61 pedagang. Data dikumpulkan berdasarkan dari hasil observasi, wawancara mendalam, dan wawancara terstruktur. Penelitian ini menggunakan uji Wilcoxon untuk menguji dampak program revitalisasi terhadap pendapatan pedagang di Pasar Petang Kabupaten Badung. Berdasarkan hasil pengolahan data mengenai dampak revitalisasi pasar tradisional terhadap pendapatan pedagang memperoleh nilai Asymp.Sig. (2-Tailed) adalah 0,008 dan untuk nilai uji satu sisi angka tersebut dibagi dua sehingga menjadi 0,004 maka H1 diterima. Hal ini berarti terdapat peningkatan pendapatan pedagang setelah dilaksanakannya program revitalisasi di Pasar Petang Kabupaten Badung.